Partner market opportunities and union formation over the life course: a comparison of different measures - Eckhard, Jan; Stauder, Johannes (Population, space and place, 2019)
Even in the online dating era, individuals will seek intimate partners who live physically nearby. This paper considers the validity of different partner market measures in German NUTS-3 regions; the often used sex ratio is contrasted with different versions of the availability ratio (AR) and versions of the partner market density (PMD). The paper discusses (a) how conceptional aspects of the partner market are reflected in the various indicators. Using aggregated population data provided by German statistical offices, (b) the partner market in Germany is described as measured by the different partner market indicators. Linking them to micro-level data from the German Socio-economic Panel, the paper (c) compares the effects of the various partner market measures on union formation. A simple sex ratio does not show variance over the life course or between cohorts, nor does it determine the rate of couple formation. The AR and PMD reveal more plausible distributions by age and cohort and higher criterion validity, especially when accounting for availableness according to marital status. With regard to men, the AR demonstrates the strongest impact on union formation; with regard to women, PMD seems more important.
Online veröffentlicht: 30. Juli 2018
Gesehen am 05.09.2018